Noise source identification for ducted fans - Bennett, Gareth J. (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2006)
Understanding combustion noise source mechanisms, designing efficient acoustic liners and optimising active control algorithms for noise reduction requires the identification of the frequency and modal content of the combustion noise contribution. Coherence-based noise source identification techniques have been developed which can be used to identify the contribution of combustion noise to near and far-field acoustic measurements of aero-engines. A number of existing identification techniques from the literature, as well as some new techniques, are implemented and evaluated under controlled experimental conditions. A series of tests are conducted to examine the efficacy of each of the procedures for specific applications. An experimental rig was designed and built to gain a fundamental physical understanding of the convection of combustion noise through the turbine of an aero-engine. The identification techniques are applied to this rig, with the objective of separating the pressure field into its constituent parts.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin